Metode Multisensori Berbasis Multimedia Digital untuk Meningkatkan Kemampuan Mengenal Huruf Hijaiyah pada Anak Usia Dini - Sessiani, Lucky Ade (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Children are in the early stage of learning. The commonly used term: “the golden age” refers to many advantages in learning process, because a child is on their peak of brain development. One of children’s development task is to prepare to learn to read, it means they need to be stimulated. Children have to master some basics in order to be able to read. As in learning to read Quran, children need to recognize the Arabic letters in Quran, called hijaiyah letters. There are 30 hijaiyah letters, more than the letters in the alphabet. This study aims to examine the effectiveness of digital multimedia-based multisensory methods in improving hijaiyah letters recognition on children at age 4 to 5 years old. The multisensory method is a well-known method to teach reading in children. In this study, multisensory method was implemented by using digital multimedia resources (computer and gadget) in order to gain more advantages in multimedia learning. The experiment was using the pretest-posttest control group design, involving 8 children each, in experiment and control groups. Result shows that there is significant difference between the pretest and posttest score in experiment group, but not in the control group. The Wilcoxon Signed Ranks Test shows significance Asymp.Sig. at 0.012 (<0.05). The Mann-Whitney (U-Test) also shows significance Exact.Sig. at 0.015 (<0.05), by comparing the posttest score between experiment and control group. It shows evidence that the method is effective to improve hijaiyah letter recognition skill in early childhood.